PSXIV-3 Expression of genes within the methionine-folate cycle are altered by glucose and one-carbon metabolite supplementation in bovine embryonic fibroblasts. (5th December 2019) - Crouse, Matthew S; Caton, Joel; Dahlen, Carl; Borowicz, Pawel; Ward, Alison
Abstract: We hypothesized that supplementation with one-carbon metabolites (OCM; methionine, folate, choline, and vitamin B12) in divergent glucose media would alter expression of genes in the methionine-folate cycle of DNA methylation in bovine embryonic tracheal fibroblasts. Cells were cultured in EMEM medium containing 1 g/L (Low) or 4.5 g/L (High) of glucose with no added OCM (CON), or 2.5, 5, or 10 times folate, choline, and B12 (2.5X, 5X, or 10X, respectively) in the CON media. Methionine was limited to 2X CON. The data were analyzed as a completely randomized design with a 2 × 4 factorial arrangement of treatments. Cells were passaged three times in treated media before RNA extraction. Gene expression analysis was conducted on Methionine Adenosyltransferase 2A and 2B (MAT2A and MAT2B) DNA Methyltransferase 1, 3A, and 3B (DNMT1, DNMT3A, and DNMT3B), S-Adenosylhomocysteine Hydrolase (AHCY), and Methionine Synthase (MTR). There was no glucose × OCM interaction for DNMT1, DNMT3A, DNMT3B, AHCY, or MTR (P > 0.17). Expression of MAT2B was greater (P < 0.01) in 2.5X, 5X, and 10X OCM in High media compared with all other treatments. Expression of DNMT1 was greater in CON, 5X, and 10X OCM in Low media compared with all other treatments. Expression of MTR was greater (P = 0.03) in CON and 10X OCM treatments compared with 2.5X and 5X levels. Finally, MAT2A and AHCY expression was affected by glucose level, with MAT2A being greater (P = 0.02) in Low compared with High, and AHCY being greater (P < 0.01) in High compared with Low media. These data suggest that glucose and OCM supplementation differentially affect the expression of genes in the methionine-folate cycle of DNA methylation. Additionally, these data demonstrate that additional work elucidating the changes in protein abundance of these enzymes, concentrations of methionine-folate cycle intermediates (specifically S-adenosylmethionine:S-adenosylhomocysteine), as well as changes in DNA methylation are needed.